Exposé historique d’une question : le risque de tremblement de terre dans la province de Québec - Parizeau, Gérard (Assurances)

(untitled) (HEC Montréal, 1989)
We proposed to Mr. Gérard Parizeau, founder of our journal, to publish an article on earthquakes which appeared in Assurances in 1966. He was happy to grant us our wish, but did ask that we warn the readers that many aspects covered in the article have changed considerably since then, and also that reinsurance will present serious problems as long as the tax authorities do not agree to set up reserves, spread over the desired number of years, to face the risks in question. We thank Mr. Parizeau, as we are convinced that the subject matter is still current, at least in general. Here are some extracts taken from two articles by the author and which were published in Assurances.